CFD Simulation on the Flow Inside a Fish Culture Tank - Ryan Anugrah Putra; Habib Luthfi Ash Shiddiqie; Hafidh Naufal Ahmad; Akhlisa Nadiantya Aji Nugroho (LPPM Politeknik Aceh Selatan, 2022)
Aquaculture is an important sector for providing a food source. Technology may help the development of aquaculture including in the design of the fluid flow condition beneficial for aquaculture tank design and its operational parameters. In this study, the use of Computational Fluid Dynamics (CFD) to provide local fluid flow information was demonstrated. In the first case, the fluid flow condition generated by two different inlet orientations, namely the straight inlet and the angled inlet was investigated. The significant difference in the fluid flow pattern was observed by the help of the velocity streamlines. In the second case, the transient CFD simulation was used to determine the transient temperature distribution for the two different inlet orientations. The result also shows the significant different in the distribution which closely related to the generated fluid flow by both inlet orientations.